Menyorot Kesenjangan Penanaman Nilai-Nilai Etika di SD Negeri 062 Tabone - Lutfi, M.; Achruh, Andi; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify the forms of social disparities in the inculcation of ethical values in Tabone Public Primary School 062 as well as analyze the role of teachers, parental parenting patterns, and the environment in addressing such inequalities through an inclusive and educational approach to education. The social disparities that occur in schools are often triggered by differences in socioeconomic status, parenting patterns, as well as the influence of learners residential environments. The study used a descriptive qualitative approach with data collection techniques through observation and interviews. The results of the study indicate that teachers have a central role as educators, coaches, and guides in helping learners deal with the social challenges they experience. Additionally, positive parenting patterns of parents as well as a supportive environment also contribute to a childs social and psychological development. Public School 062 Tabone has made various efforts to reduce social disparities, such as through Islamic Religious Education-based counseling guidance, moral learning, teacher example, and the application of punishment of an educational nature. This study affirms the importance of a multidimensional approach in addressing social inequalities in school environments in order to create an inclusive and equitable education.